Tác động của kết nối liên tục đến địa vị nhân viên: Thông qua vai trò trung gian của thỏa mãn nhu cầu tâm lý cơ bản và vai trò điều tiết của tham gia công việc - Phan Hà Thanh, Nhã; Nguyễn Thị Mai , Trang (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
Constant connectivity is increasingly vital in the workplace due to its convenience, greater flexibility, and the freedom to work anywhere and anytime. This study examines how constant connectivity affects employees’ status through basic psychological needs satisfaction, with a moderating role of job involvement. A sample of 260 employees was used to test the proposed model and PLS-SEM method. The finding revealed that constant connectivity impacted employee status. The autonomy, competence, and relatedness needs positively mediate the relationship between constant connectivity and employee status. Job involvement functions as an enhancer for the effect of constant connectivity on competence and relatedness needs satisfaction. Implications for theory and management practices are discussed in this study.
Keywords: Constant connectivity to; Psychological need; Employee status; Job involvement